Students’ trust toward AI-generated outcomes in English Language learning - Pamungkas, Firdaus Ditya; Akbarani, Rizqi (Priviet Social Sciences Journal, 2026)
ABSTRACT The emergence of Artificial Intelligence in the education sector has risen rapidly. AI offers several conveniences, particularly for university students, as a tool that can help overcome the challenges of academic learning. However, students do not full and uncritically trust the outcomes generated by AI. This study aimed to explore the extent of students’ trust in AI-generated outcomes in English language learning. A descriptive qualitative was employed, with a questionnaire used as the primary data collection instrument. The participants of this study were 30 first year university students from non-English program at the same institution. The results indicates that while students generally perceive AI outcomes as beneficial for learning English, they continue to use AI as a supportive too rather than as a substitute for completing all academic tasks. In addition, students tend to use AI only when academic tasks or specific learning needs require it, rather than relying on it continuously. Overall, AI serves as an effective support for students in English language learning when used appropriately and its suitable contexts. Keywords: students’ trust, AI outcomes, higher education, English language learning